Neural architecture : design and artificial intelligence - Campo, Matias del (Applied Research and Design Publishing, an imprint of ORO Editions, 2022)
This book explores the interdisciplinary project that brings the long tradition of humanistic inquiry in architecture together with cutting-edge research in artificial intelligence. The main goal of Neural Architecture is to understand how to interrogate artificial intelligence - a technological tool - in the field of architectural design, traditionally a practice that combines humanities and visual arts. Matias del Campo, the author of Neural Architecture is currently exploring specific applications of artificial intelligence in contemporary architecture, focusing on their relationship to material and symbolic culture. AI has experienced an explosive growth in recent years in a range of fields including architecture but its implications for the humanistic values that distinguish architecture from technology have yet to be measured. The book illustrates in a series of projects a set of crucial questions for the development of architecture in the future. An opportunity to survey the emerging field of Architecture and Artificial Intelligence, and to reflect on the implications of a world increasingly entangled in questions of the agency, culture and ethics of AI.